Anthropogenic controls on overwash deposition: Evidence and consequences. Issue 12 (29th December 2015) - Rogers, Laura J.; Moore, Laura J.; Goldstein, Evan B.; Hein, Christopher J.; Lorenzo‐Trueba, Jorge; Ashton, Andrew D.
Abstract: Accelerated sea level rise and the potential for an increase in frequency of the most intense hurricanes due to climate change threaten the vitality and habitability of barrier islands by lowering their relative elevation and altering frequency of overwash. High‐density development may further increase island vulnerability by restricting delivery of overwash to the subaerial island. We analyzed pre‐Hurricane Sandy and post‐Hurricane Sandy (2012) lidar surveys of the New Jersey coast to assess human influence on barrier overwash, comparing natural environments to two developed environments (commercial and residential) using shore‐perpendicular topographic profiles. The volumes of overwash delivered to residential and commercial environments are reduced by 40% and 90%, respectively, of that delivered to natural environments. We use this analysis and an exploratory barrier island evolution model to assess long‐term impacts of anthropogenic structures. Simulations suggest that natural barrier islands may persist under a range of likely future sea level rise scenarios (7–13 mm/yr), whereas developed barrier islands will have a long‐term tendency toward drowning. Key Points: Residential (commercial) buildings reduce overwash deposition by 40% (90%) Development effectively filters high‐frequency overwash events Model results predict that reduction in overwash deposition leads to island drowning